2017
DOI: 10.1002/elan.201700146
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NADH Oxidation Using Polytyramine/Carbon Nanotube Modified Electrodes for Ethanol Biosensing

Abstract: Polytyramine (PT) has been electro‐deposited onto multi‐walled carbon nanotube (MWCNT) modified glassy carbon (GC) electrodes via oxidation of tyramine in 0.1 M H3PO4 by cycling the potential over the range of −400 mV to 1300 mV (versus Ag/AgCl). The reactivity of the resulting chemically‐modified electrodes was characterized using cyclic voltammetry in the presence and absence of reduced nicotinamide adenine dinucleotide (NADH). The modified electrodes displayed electrochemical activity due to the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Upon electropolymerization of tyramine at both GC/GraphC and GC/CVD‐MWCNT electrodes, multiple processes emerge with repetitive cycling. These redox couples have been attributed to the formation of quinone functional groups . This survey of the voltammograms revealed that substantial variation in the nature of PT and quinone functional groups occurred upon electropolymerization.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Upon electropolymerization of tyramine at both GC/GraphC and GC/CVD‐MWCNT electrodes, multiple processes emerge with repetitive cycling. These redox couples have been attributed to the formation of quinone functional groups . This survey of the voltammograms revealed that substantial variation in the nature of PT and quinone functional groups occurred upon electropolymerization.…”
Section: Resultsmentioning
confidence: 97%
“…We have recently reported polytyramine (PT) is a suitable candidate for use as a NADH oxidation mediator in biochemical applications . Tyramine oxidation in acidic media results in electropolymerization occurring through the ortho ‐position of the phenol moiety, leading to a polymer that carries free amino groups for potential enzyme immobilization .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The great limitation of dehydrogenase‐based systems in general, and NAD + ‐dehydrogenase‐based systems, in particular, is that, in contrast to oxidases, which have redox cofactors tighly bound to the enzyme, the cofactors are not bound to the enzyme, and it is necessary to add them to perform each determination . In fact, most of dehydrogenase‐based biosensors involve the addition of NAD + cofactor to the supporting electrolyte , but it makes the determination time‐consuming and expensive. Therefore, new strategies are required for the construction of reagentless dehydrogenase‐based electrochemical biosensors in which both, the enzyme and NAD + , are effectively immobilized onto the electrode in such a way that the cofactor has easy acces to the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Tyramine is also a redox mediator containing quinone species which display catalytically active towards NADH oxidation. Wilson et al . electrochemically deposited a layer of Poly(tyramine) (PT) on a MWCNT‐covered GCE where NADH was oxidized around 0.2 V. Another redox mediator of quinone family, pyrroloquinoline quinone (PQQ), was ultra‐sonically mixed with graphene fragments and the composite materials were self‐assembled on the surface of a chitosan‐coasted GCE .…”
Section: Introductionmentioning
confidence: 99%